Mechanical strain engineering of dielectric tunability in polycrystalline SrTiO3 thin films. Issue 10 (23rd February 2018) - Tkach, Alexander; Okhay, Olena; Reaney, Ian M.; Vilarinho, Paula Maria
Abstract : Relative permittivity, ε r, and dielectric tunability, η, of polycrystalline ST films optimised via compressive stresses, ex: ST films on MgO/Pt substrates. Abstract : Optimizing performance using low cost scalable processing and substrates is critical if functional oxide thin films are to achieve commercialisation. Here, we present a comprehensive investigation of the role of low cost Al2 O3, SrTiO3, and MgO substrates in the structure, microstructure and electrical properties of SrTiO3 (ST) thin films, deposited by sol–gel processing. We demonstrate that the dielectric properties of polycrystalline ST films depend on the strain/stress induced by the substrates. ST films deposited on Al2 O3 /Pt substrates under a high tensile stress possess the smallest grain size and present the lowest value of the relative permittivity, ε r, with the lowest dielectric tunability. In contrast, ST films deposited on MgO/Pt substrates, under the highest compressive stress, have the highest value of ε r, tunability and polarization. It is thus demonstrated that for polycrystalline ST films the relative permittivity and dielectric tunability may be optimised through an induced compressive stress state.